Penguatan Literasi Politik dan Bahasa Inggris melalui Media-Content Based bagi Siswa/i Madrasah - Yurial Arief Lubis; Soraya Grabiella Dinamika; Muhammad Muslim Nasution; Yoni Rahayu (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2026)
The development of digital democracy in Indonesia requires the younger generation to have adequate political and media literacy to understand and critically evaluate public information. However, the integration of political literacy, media literacy, and English language learning in madrasahs is still limited. This Community Service activity aims to improve madrasah students' political literacy and their ability to produce and disseminate public information through English-language media. The activity was held on October 9-10, 2025, at MAS SKB 3 Menteri Sei Tontong, involving 28 students as participants. The implementation method used a project-based learning approach, which included the delivery of political literacy material, training in English political vocabulary, and assistance in creating digital media content using the Canva application. Evaluation was carried out through pre-tests and post-tests, which were analyzed using the N-gain formula. The results of the activity showed an increase in participants' understanding, with most of the questions falling into the high category. In addition, the students were able to produce English-language media content containing educational information on public issues in Indonesia. This activity shows that the integration of political literacy, media literacy, and English language learning through digital content production can be an effective approach.